THE CHARACTER ANALYSIS OF THE MAIN CHARACTERS AND THE SUBORDINATE CHARACTERS IN DILAN 1990 MOVIE AS A STUDY OF LITERARY PSYCHOLOGY - Meiva Eka Sri Sulistyawati; Chodidjah; Adelia Taufinata (Jurnal Metamorfosa, 2020)
Cinema and Literature are two distinct but equally extraordinary works of art. Though both these arts have certain connections and differences, both have a similarity of taking its readers/audience to a different world. The purpose of this study is to analyze the characters of the main and subordinate characters through a review of a study of literary psychology. The data source in this study uses a film entitled Dilan 1990 which is created by Pidi Baiq. The research methodology used in this study is descriptive qualitative using the library method and also structural assessment in making work designs. In connection with the results of the analysis of this study it can be recommended that this analysis be suitable to be presented to us since it has many positive values to give us a lesson. Like loving each other, being honest, and achieving the highest achievement. Key Words: cinema, film, literature, literary psychology, library method